Microcrystalline silicon thin films prepared by RF reactive magnetron sputter deposition - Cerqueira, M. F. (1995)
Hydrogenated microcrystalline silicon (microc-Si:H) thin films with Cu as a dopant material (about 2 wt.%) were deposited by RF planar magnetron sputtering in an argon/hydrogen plasma. The composition and microstructure of the films were analysed by SEM, ERD/RBS, X-ray diffraction and Raman spectroscopy. These techniques revealed a columnar film structure, each column consisting of several small (nano) crystals with a lateral dimension up to 10nm. The crystals are oriented, generally with the (111) plane parallel to the sample surface. The hydrogen content of the thin films is about 27-33 at.%. Low deposition rates and low sputter gas pressures favour crystallisation and grain growth. The behaviour can be understood in terms of the diffusion or relaxation length of the deposited Si-atoms.